Are Turkish elite sailors competing in Laser and 470 classes ready for the Olympics? - Cinar-Medeni, Ö.; Pekyavas, N. O.; Uzun, A.; Er, F.; Suveren, C.; Colakoglu, F. F.; Baltaci, G. (Medicina dello Sport, 2017)
BACKGROUND: Aerobic and anaerobic capacity, muscle strength and balance skills are important parameters in sailors. We aimed to investigate the aerobic and anaerobic capacity, knee muscle strength, hand grip strength and balance of elite Turkish sailors competing in 470 and Laser classes selected for the Olympic team and to establish the differences in physical fitness status between sailors competing in 470 and Laser classes. METHODS: Nine Laser and ten 470 sailors were evaluated. A treadmill VO2max test for aerobic capacity, a Wingate cycle ergometer test for anaerobic power and capacity, an isokinetic knee muscle strength assessment at 60°/s and 120°/s angular velocities (output data were flexor peak torque, extensor peak torque and H/Q strength ratio), an isometric hand grip strength assessment and a star excursion balance test (SEBT) were performed. RESULTS: Laser and 470 sailors showed similar physical fitness values and no difference was found between sailing classes (P>0.05) for all test results. Most of the sailors` H/Q strength ratios were lower than normal values. CONCLUSIONS: This study shows that the physical requirements of Laser and 470 sailors are similar; however, they are both at risk of knee injury because of low H/Q strength ratios. Athletic trainers and physiotherapists working with sailors should also consider the H/Q strength ratio because low values of H/Q strength ratio are seen in this population. The results of this study may constitute a basis for further studies because we have reported the results of several physical fitness tests together and in a detailed manner.